PENGARUH METODE PEMBELAJARAN ROLE PLAYING TERHADAP HASIL BELAJAR SISWA MATA PELAJARAN BAHASA INDONESIA SISWA KELAS IV SDN PINANG 2 KOTA TANGERANG - Eka Listiani; Septy Nurfadhillah; Rizki Zuliani (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
This study aims to determine whether there is an influence of roleplaying learning methods on the learning outcomes of students of subjects Indonesian grade IV students of SDN Pinang 2 Tangerang City. This research was conducted at SDN Pinang 2 Tangerang City. From the interview results, there were 78% of students who achieved KKM scores and 22% who had not achieved KKM scores from a total of 32 students, in the learning process there were still students who were less active during learning and the method often used by teachers was conventional methods. The research method used is pre-experimental. The sampling amounted to 63 students with class IV A totaling 32 students as the experimental class and class IV B totaling 31 students as the control class. From the results of the posttest hypothesis test conducted using an independent sample test (t-test), sig was obtained. 2 tailed (0.008) < sig. α (0,05). From the hypothesis test it can be concluded that H_0 rejected and H_1 accepted. The results of this study show that there is an influence of roleplaying methods on the learning outcomes of Indonesian language students in grade IV at SDN Pinang 2 Tangerang City. So it can be concluded that there is an influence between the role playing method on the Indonesian learning outcomes of grade IV students of SDN Pinang Kota Tangerang. Keywords: Role Playing, Indonesian, Learning Outcomes